Not exactly in praise of vagueness - "Deemter,Kees Van" (Oxford, 2010)
Not everything is black and white. Our daily lives are full of vagueness or fuzziness. Language is the most obvious example - for instance, when we describe someone as tall, it is as though there is a particular height beyond which a person can be considered 'tall'. Likewise the terms 'blond' or 'overweight' in common usage. We often think in discontinuous categories when we are considering something continuous. In this book, van Deemter cuts across various disciplines in considering the nature and importance of vagueness. He looks at the principles of measurement, and how we choose categories; the vagueness lurking behind what seems at first sight crisp concepts such as that of the biological 'species'; uncertainties in grammar and the impact of vagueness on the programmes of Chomsky and Montague; vagueness and mathematical logic; computers, vague descriptions, and Natural Language Generation in AI (a new class of programs will allow computers to handle descriptions such as 'the man in the yellow shirt'). Van Deemter shows why vagueness is in various circumstances both unavoidable and useful, and how we are increasingly able to handle fuzziness in mathematical logic and computer science.
Keywords: Vagueness